TGN38 recycles basolaterally in polarized Madin-Darby canine kidney cells. - Rajasekaran, A; Humphrey, J; Wagner, M; Miesenböck, G; Le Bivic, A; Bonifacino, J; Rodriguez-Boulan, E (1994)
Sorting of newly synthesized plasma membrane proteins to the apical or basolateral surface domains of polarized cells is currently thought to take place within the trans-Golgi network (TGN). To explore the relationship between protein localization to the TGN and sorting to the plasma membrane in polarized epithelial cells, we have expressed constructs encoding the TGN marker, TGN38, in Madin-Darby canine kidney (MDCK) cells. We report that TGN38 is predominantly localized to the TGN of these cells and recycles via the basolateral membrane. Analyses of the distribution of Tac-TGN38 chimeric proteins in MDCK cells suggest that the cytoplasmic domain of TGN38 has information leading to both TGN localization and cycling through the basolateral surface. Mutations of the cytoplasmic domain that disrupt TGN localization also lead to nonpolarized delivery of the chimeric proteins to both surface domains. These results demonstrate an apparent equivalence of basolateral and TGN localization determinants and support an evolutionary relationship between TGN and plasma membrane sorting processes.